KEBIJAKAN SALURAN PEMASARAN GELAMAI PERENTAK BANGKO - Ahmad Tarmizi (Universitas Batanghari Jambi, 2010)
Company gelamai perentak Bangko is sala a small company of three companies that produce similar snacks, such gelamai or better known as dodol. This business is located in jl. M. Yamin on the Bangko market. Company gelamai very strategic cross roads located in Bangko-Kerinci. During the period of 5 years from 2005 until 2009, these efforts have increased sales volume high enough on average 23.6% per year. But under his rule, shere market trends show a decline, in 2005 amounted to 37.8% and in 2009 dropped to 29.4%.These companies in marketing their products using a surrogate way to the shops or to retailers. Furthermore, the distribution of its products, this business using indirect channels and direct distribution channels by involving as many as 15 stores in Bangko, 30 retailers who are in the marketing area of Jambi province that includes:Jambi, county Batanghari, county Merangin, Bungo and Kerinci district. Meanwhile, outside the marketing area outside the province jambi / non-local namely propinssi southern Sumatra and West Sumatra provinces. As well as using two agents are individual agents who worked on local and regional Bungo western Sumatra and agents who serve the supermarket HWPI sun and theater department. in 2007 until the year 2010 the company began to expand the marketing area of Sumatra sumatra west and south.Key word : policies, channel ordering, gelamai